An access control and authorization model with Open stack cloud for Smart Grid - Rathod, Yagnik A (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2020)
In compare to Authentication for identification and relationship of an identity of a user with its task and process within the system, authorization in access control is much anxious about confirming that user and its task in the form of system process, access to the assets of any particular domain is only approved when proven obedient to the identified policies. Access control and authorization is always an area of interest for researchers for enhancing security of critical assets from many decades. Our prime focus and interest is in the field of access control model based on Attribute base access control (ABAC) and with this paper we tried to integrate ABAC with openstack cloud for achieving finer level of granularity in access policies for domain like smart grid. Technical advancement of current era demands that critical infrastructure like traditional electrical grid open ups to the modern information and communication technology to get the benefit in terms of efficiency, scalability, accessibility and transparency for better adaptability in real world. Incorporation of ICT with electric grid makes it possible to do greater level of bi-directional interaction among stake holders like customer, generation units, distribution units and administrations and these leads international organization to contribute for standardization of smart grid concepts and technology so that the realization of smart grid becomes reality. Smart grid is a distributed system of very large scale by its nature and needs to integrate available legacy systems with its own security requirements. Cloud computing proven to be most efficient approach for said requirements and we have identified openstack as our cloud platform. We have integrated ABAC approach with default RBAC approach of openstack and provide a frame work that supports and integrate multiple access control polices in making authorization decisions. Smart grid domain in considered as case study which requires support of multiple access policies (RBAC, ABAC or DAC etc) with our model for access control and authorization.